“Somethings About Me”: Slanted Conventions in Children’s Letters to Beloved Authors - Kuecker, Elliott (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
This article is a study of letters written by American children to authors of juvenile fiction. It emphasizes the rhetorical and material choices children made in bridging the distance between themselves as writers and the authors who were to receive the letters. Focused on notions of convention, the study uses the theoretical concept of the slant to analyze the way the child writers conformed to conventions of writing and communication while also rendering those expectations askew. Ultimately, the stylistic techniques and content choices reveal methods children used to cocreate a world with the authors to whom they wrote.